On the self-regulation of sport practice: Moving the narrative from theory and assessment toward practice - Young, Bradley W.; Wilson, Stuart G.; Hoar, Sharleen; Bain, Lisa; Siekańska, Malgorzata; Baker, Joseph (Frontiers in Psychology, 2023)
This paper reviews theoretical developments specific to applied research around the ‘psychology of practice’ in skill acquisition settings, which we argue is under-considered in applied sport psychology. Centered upon the Self-Regulation of Sport Practice Survey (SRSP), we explain how self-regulated learning conceptually underpins this survey and review recent data supporting its empirical validation for gauging athletes’ psychological processes in relation to sport practice. This paper alternates between a review of applied research on self-regulated sport practice and new data analyses to: (a) show how scores on the SRSP combine to determine an expert practice advantage; and (b) illustrate the large scope of self-organized or athlete-led time to which SRSP processes may apply. At this stage, the SRSP has been established as a reliable and valid tool in the empirical, theoretical domain. In order to move the narrative from theory and assessment towards applied practice, we present evidence to propose that it has relevance as a dialogue tool for fostering meaningful discussions between athletes and sport psychology consultants. We review initial case study insights on how the SRSP could be located in consultation in professional practice, propose initial considerations for its practical use and invite practitioners to examine its utility in applied settings.